Influence of Materialistic Value and Fear of Missing Out (FoMO) on Financial Decisions of Active Instagran and TikTok User Among Students - Aulia Mulki; Asriany Asriany; Riyanti Riyanti (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the influence of materialistic value and Fear of Missing Out (FoMO) on the financial decision-making of university students who are active Instagram and TikTok users. This study is important for understanding the psychological factors that influence financial behaviour in the digital era. Methodology: This study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 university students in Palopo City, selected using purposive sampling. The data were analysed using multiple linear regression with SPSS. Results: The findings indicate that materialistic value does not have a significant effect on financial decisions, while FoMO has a positive and significant effect on students’ financial decision-making. Simultaneously, both variables significantly influence financial decisions. These findings suggest that psychological pressure and social comparison driven by social media use contribute to students’ financial behaviour. Novelty: This study integrates materialistic value and FoMO in analysing financial decision-making among students who are active users of social media, particularly Instagram and TikTok.  Conclusion: Students’ financial decisions are influenced more by psychological and social factors than by purely rational considerations. Type of Paper: Research Article.